Teachers’ role in shaping fourth-grade students’ character through Pancasila education at Bringin 02 Elementary School - Ladya Fairusy Naja; Susilo Tri Widodo (Jurnal Prima Edukasia, 2026)
National education aims to develop the potential of students to become people who are faithful, have noble morals, and have character in accordance with the noble values ​​of Pancasila. The purpose of this study is to explain the role of teachers in shaping students’ character through Pancasila education in fourth-grade students of Bringin 02 Public Elementary School. The type of research used is a case study, with a qualitative approach. Primary data sources such as fourth-grade students and homeroom teachers, and secondary data in the form of articles, books and others relevant to the research. Data collection techniques consist of observation, interviews, and documentation, then analyzed using techniques namely data collection, data reduction, data presentation and conclusions. The validity of the research data is tested with Credibility Test and Confirmability Test. The results of the study indicate that the character of good manners of fourth-grade students requires consistent habituation through Pancasila Education. Teachers have carried out the roles of educators, motivators, and evaluators optimally. Supporting factors involve role models and self-will, while obstacles include low awareness and negative influences from the peer environment. Keywords: Teacher Role, Character, Pancasila Education, Grade IV Elementary School Students.